University Social Responsibility and Quality of Life : A Global Survey of Concepts and Experiences - Shek, Daniel T. L.; Hollister, Robert M. (Springer Singapore : Imprint: Springer, 2017)
This book provides a critical review of the theory and practice of University Social Responsibility. In addition to addressing the nature of and concepts surrounding University Social Responsibility, as well as its ties to areas such as service learning or engaged scholarship, the book also presents effective practices from around the world. Dedicated chapters demonstrate how University Social Responsibility can manifest itself in different types (civic, moral, economic or global responsibility), levels (local, national, regional or international), and formats (partnership, venture or joint project), depending on local contexts and needs. The book also focuses on three areas of work - educating students to take on social responsibility, broadening access to education, and applying knowledge to societal problems - to highlight the potential and viable ways University Social Responsibility can be employed to promote quality of life in society. Offering a unique resource, it is intended to stimulate thinking and expand the repertoire of all educators, administrators, and organizations who wish to incorporate societal needs into their core mission and promote quality of life in different communities around the world.
Keywords: Social sciences.; Social responsibility of business.; Medical research.; Higher education.; Welfare economics.; Quality of life.; Social service.; elektronické knihy; electronic books